The causes and consequences of trained immunity in myeloid cells - Bhargavi, Gunapati; Subbian, Selvakumar (Frontiers in Immunology, 2024)
Conventionally, immunity in humans has been classified as innate and adaptive, with the concept that only the latter type has an immunological memory/recall response against specific antigens or pathogens. Recently, a new concept of trained immunity (a.k.a. innate memory response) has emerged.According to this concept, innate immune cells can exhibit enhanced responsiveness to subsequent challenges, after initial stimulation with antigen/pathogen. Thus, trained immunity enables the innate immune cells to respond robustly and non-specifically through exposure or re-exposure to antigens/infections or vaccines, providing enhanced resistance to unrelated pathogens or reduced infection severity. For example, individuals vaccinated with BCG to protect against tuberculosis were also protected from malaria and SARS-CoV-2 infections. Epigenetic modifications such as histone acetylation and metabolic reprogramming (e.g. shift towards glycolysis) and their inter-linked regulations are the key factors underpinning the immune activation of trained cells. The integrated metabolic and epigenetic rewiring generates sufficient metabolic intermediates, which is crucial to meet the energy demand required to produce proinflammatory and antimicrobial responses by the trained cells. These factors also determine the efficacy and durability of trained immunity. Importantly, the signaling pathways and regulatory molecules of trained immunity can be harnessed as potential targets for developing novel intervention strategies, such as better vaccines and immunotherapies against infectious (e.g., sepsis) and non-infectious (e.g., cancer) diseases. However, aberrant inflammation caused by inappropriate onset of trained immunity can lead to severe autoimmune pathological consequences, (e.g., systemic sclerosis and granulomatosis). In this review, we provide an overview of conventional innate and adaptive immunity and summarize various mechanistic factors associated with the onset and regulation of trained immunity, focusing on immunologic, metabolic, and epigenetic changes in myeloid cells. This review underscores the transformative potential of trained immunity in immunology, paving the way for developing novel therapeutic strategies for various infectious and non-infectious diseases that leverage innate immune memory.